Simultaneous Determination of 35 Organic Metabolites Including Amino Acids, Creatine, Creatinine, and Oxidized and Reduced Glutathione in Lung Tissue, Plasma and Urine Using Liquid Chromatography–Tandem Mass Spectrometry. (11th February 2020) - Seo, Chan; Hwan Kim, Sung; Lee, Hyeon-Seong; Park, Hyung-Jin; Kim, Youngbae; Ji, Moongi; Min, Jeuk; Oh, Shong-Jin; Lee, Kyuhong; Paik, Man-Jeong
Abstract: A simple and rapid method for the simultaneous determination of 35 non-derivatized metabolites was developed using liquid chromatography – tandem mass spectrometry. Under the optimal conditions, linearity was achieved in the range from 0.05 to 10.0 ng ( R 2 ≥ 0.989). The repeatability provided percentage relative standard deviations ≤11.2 and a trueness expressed as percentage relative error from −10.7% to 12%. The recoveries ranged from 87.3% to 109.8% with good repeatability. When applied to mouse lung tissue, plasma, and urine samples, 30 amino acids, creatine, creatinine, and oxidized glutathione were positively identified and quantified. The described present method was useful for the simultaneous determination of amino acids, creatine, creatinine, and oxidized glutathione in biological samples, including tissue, plasma, and urine.